2016
DOI: 10.1186/s12889-016-2697-6
|View full text |Cite
|
Sign up to set email alerts
|

Niche modeling predictions of the potential distribution of Marmota himalayana, the host animal of plague in Yushu County of Qinghai

Abstract: Background: After the earthquake on 14, April 2010 at Yushu in China, a plague epidemic hosted by Himalayan marmot (Marmota himalayana) became a major public health concern during the reconstruction period. A rapid assessment of the distribution of Himalayan marmot in the area was urgent. The aims of this study were to analyze the relationship between environmental factors and the distribution of burrow systems of the marmot and to predict the distribution of marmots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 26 publications
(43 reference statements)
1
22
0
Order By: Relevance
“…ENM method is an especially effective method to predict the potential risks of a disease [ 37 39 ], as identifying the potential risk distribution of human disease is a very complex task [ 40 ]. Among the numerous ENM methods, Maxent has been identified as the best algorithm [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…ENM method is an especially effective method to predict the potential risks of a disease [ 37 39 ], as identifying the potential risk distribution of human disease is a very complex task [ 40 ]. Among the numerous ENM methods, Maxent has been identified as the best algorithm [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human cases have been used as presence data in a number of previous studies to develop ENMs for determining potential vector distribution in different settings [20, 71, 72]. …”
Section: Methodsmentioning
confidence: 99%
“…The first approach involves modeling the species, with occurrence data, that participate in the transmission cycle [14, 16, 74] while the second approach analyzes the distribution of disease occurrence, as if it was a species, considering the entire transmission cycle and its ecological relationships [20, 71, 72]. In addition to this, P. argentipes has been shown to be the single proven vector of L. donovani in the study area [50]; thus, its distribution could reasonably be determined by the same environmental variables used to model the distribution of the disease.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The paralysis of disease surveillance and control system were caused by the earthquake, the conditions conducive to the occurrence and spread of infectious diseases were increased, therefore, the most important content in the earthquake relief work was preventing the outbreak of anthropozoonosis. After the disaster, the veterinarian department actively devoted in the epidemic prevention work, and it showed that the veterinarian played an important role in the prevention and control work of anthropozoonosis after the disaster [1][2][3]. In fact, the veterinarian participated in the earthquake relief work of Indian Ocean Tsunami and Kashmir Earthquake in 2005.…”
Section: Introductionmentioning
confidence: 99%